2010
DOI: 10.1080/19390450903350838
|View full text |Cite
|
Sign up to set email alerts
|

Household Consumption and Natural Resource Management around National Parks in Zambia

Abstract: Game Management Areas in Zambia aim to combine nature conservation with economic empowerment of rural households. This study determines the impact of community-based wildlife management and participation in related community institutions on household welfare. The results indicate that the gains from living in Game Management Areas and from participating in natural resource management are large but unevenly distributed. Only Game Management Areas with limited alternative livelihoods exhibit significant consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 10 publications
6
37
2
Order By: Relevance
“…Unfortunately, there is little scientific evidence on the nature of this heterogeneity or the potential tradeoffs between environmental and socioeconomic outcomes (3,12). Retrospective causal analysis of the socioeconomic impacts of developing country protected areas is limited (6,10,11,13,14). Only the work in Thailand and Costa Rica (10,11,13) also included information on environmental outcomes.…”
mentioning
confidence: 99%
“…Unfortunately, there is little scientific evidence on the nature of this heterogeneity or the potential tradeoffs between environmental and socioeconomic outcomes (3,12). Retrospective causal analysis of the socioeconomic impacts of developing country protected areas is limited (6,10,11,13,14). Only the work in Thailand and Costa Rica (10,11,13) also included information on environmental outcomes.…”
mentioning
confidence: 99%
“…For example, it may be argued that the designation of forests as reserves or protected areas can impose significant human costs on the poor by excluding resource use. Alternatively, protected areas have been shown to generate important local benefits by preserving access to the resource through cooperative management and by stimulating employment from tourism growth [33,49,50]. Referring to the example of forests, Fisher [15] concluded that the activities of the wealthy, who are most likely to participate in timber extraction activities, pose a greater ecological threat to poverty and food security, leaving poor households vulnerable to the degradation and depletion of forest resources.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, however, research has found these initiatives lacking and correspondingly many refinements have been proposed. These have included calls for program designs to incorporate greater focus on cultural context (Waylen et al 2010), education (Peters 1998, Wainwright andWehrmeyer 1998), adaptive capacity (Armitage 2005), governance (Brechin et al 2002), social institutions Gibson 1999, Nelson andAgrawal 2008), social, physical, and economic capital (Garnett et al 2007), equitable distribution of benefits (Bandyopadhyay andTembo 2010, Yasuda 2011), gender issues (Wainwright and Wehrmeyer 1998), financial interfaces (Blaikie 2006), stronger connections between conservation and development goals (Martin et al 2011), and improved ecological monitoring (Kremen et al 1994). …”
Section: Introductionmentioning
confidence: 99%